Digitalisasi Pemerintahan; Analisis Implementasi SPBE pada Sekretariat Daerah Kabupaten Sumedang Berbasis Pendekatan Good Governance. - Salli Nur Afifah; Rahman Mulyawan; Novie Indrawati Sagita (Universitas Muhammadiyah Ponorogo, 2026)
Transformations Digital is one of the strategic agendas in improving the performance of bureaucracy and public services in the digital era. The Electronic-Based Government System (SPBE) is present as the main instrument in realizing more effective, efficient, and accountable governance. This study aims to analyze the implementation of SPBE at the Sumedang Regency Regional Secretariat using the good governance approach as an evaluation framework. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study show that the implementation of SPBE at the Sumedang Regency Regional Secretariat has made significant progress, especially in terms of transparency, service efficiency, and increased access to public information. However, there are several challenges in terms of coordination between regional devices, limited digital infrastructure, and uneven human resource capacity. The good governance approach that includes the principles of participation, accountability, transparency, effectiveness, and responsiveness is an important foundation in evaluating the extent to which SPBE can support bureaucratic reform at the regional level. This study recommends increasing digital training for civil servants, optimizing system integration, and strengthening cross-sector collaboration as an effort to strengthen the sustainability of digital transformation in local government environments. This finding is expected to be a reference for other regions in developing SPBE policies that are in line with the principles of good governance. Keywords: Digital Transformation; SPBE; Good Governance;